Ecologia de paisagem como subsídio à recuperação de Áreas de Preservação Permanente (APP) - Jesus, Edilma Nunes de (2018)
The intense environmental degradation in the riparian forests has resulted in a reduction in Permanent Preservation Areas (PPAs), ranging from the maintenance of river basins, survival conditions to species of fauna and flora and the surrounding riverside communities, mainly in relation to changes in soil and water resources. And, these impacts reflect the need for Degraded Area Recovery (RAD) work to be carried out in order to improve these ecosystems. However, the high costs of traditional RAD practices, coupled with the lack of information on alternative RAD models, restrict access to these techniques. In this context, nucleating techniques, whose theoretical basis originates in Landscape Ecology, has been highlighted as alternative strategies of RAD, either for the lowest costs, but also for the principle of enhancing interactions that occur naturally in the environment. Thus, the general objective of this study is to evaluate the viability of alternative RAD techniques by contributing to the rescue of connectivity between degraded and conserved areas, located in the Northeast of the State of Bahia, using the Landscape Ecology tools. For this, the present thesis also sought to identify feasible stretches for the implantation of nucleating recovery techniques from the Landscape Ecology metrics in the area under study; to analyze the environmental perception of the rural community regarding recovery practices and to monitor the nucleator processes through a matrix of environmental indicators, including the ecological, social and economic dimensions. In this sense, analyzes were applied in GIS (Geographic Information Systems) environment to characterize the structure and connectivity of the landscape, with the free extensions Patch Analyst 5.0 and Conefor Sensinode 2.2; the environmental perception was investigated to a specific public (intentional sample) from interviews and participatory workshops, measured from perceptual processes (White, 1978); and the implantation of nucleating techniques was monitored through a matrix of environmental indicators, allied to the compilation of statistical data. Therefore, it was observed that the area has elements related to the effects of fragmentation (number and size of fragments, shape and isolation conditions, etc.). However, the analysis of GIS and diagnosis carried out in loco showed that the greater proximity between the small fragments, as well as the connectivity of the areas of APP are favorable elements to the implantation of the nucleation techniques: galleria and transposition of litter. As for the environmental perception of the surrounding community, the obstacles that may interfere with the recovery actions are related to the socio-environmental problems experienced, as well as the present conflicts. However, local knowledge, the existence of targets to be conserved and the importance attributed to the recovery work point out that this activity can be intensified, mainly, through the opening of dialogue between social actors and the formation of participatory spaces. In general, the implantation of nucleating techniques in the São José do Avena (Itanagra-BA) AVC presents an opportune scenario regarding the selected and applied environmental indicators, which shows the potential that this type of activity aggregates with a view to recovery of degraded areas in the region offering multiple benefits.